POTENSI LIPID MIKROALGA AURANTIOCHYTRIUM DARI HUTAN BAKAU INDONESIA SEBAGAI BAHAN BAKU PRODUKSI BIOFUEL - Suhendra, Suhendra; Veranica, Veranica; Handayani, Nurliana; Hutari, Andri (Jurnal Chemurgy, 2024)
Microalgae's high lipid content makes them an alternative raw material for the generation of biofuel. This research examines the potential of Aurantiochytrium microalgae sourced from mangrove forests. The capacity to create omega-3 polyunsaturated fatty acids, such DHA, which have a high economic value, is one benefit of Aurantiochytrium microalgae and makes integrated production with biofuel production feasible. The possible biofuel products from Aurantiochytrium microalgae, including biodiesel and bioviation fuel, are reviewed in this research. These microalgae go through multiple steps in the biofuel production process, including isolation, cultivation, lipid extraction, and hydroprocessing and transesterification to turn the algae into biodiesel or biojet fuel. The first steps toward producing biofuel from Aurantiochytrium microalgae obtained from Indonesian mangrove forests are expected to be laid by this research.